Oridonin alters the expression profiles of MicroRNAs in BxPC-3 human pancreatic cancer cells - Gui, Zhifang (BMC Complement Altern Med, 2015)
BACKGROUND: Oridonin, an ingredient used in traditional Chinese medicine, has been demonstrated to play an important role in antitumour effects, but the mechanism underlying its antitumour properties is still not clear. METHODS: To verify the anti-cancer effects of oridonin via a miRNA-dependent mechanism, comprehensive miRNA expression profiling of oridonin-treated BxPC-3 human pancreatic cancer cells was performed using a miRNA microarray assay based on Sanger miR-Base Release 20, followed by a validation using real-time PCR. MicroRNA target prediction and Gene Ontology and KEGG pathway analysis were performed to investigate possible pathways involved. RESULTS: The results showed that 105 miRNAs were significantly differentially expressed (signal reading >500, p ≤ 0.01, |Log2-value| ≥1) in oridonin-treated BxPC-3 human pancreatic cancer cells. CONCLUSIONS: Our data indicates that oridonin inhibits BxPC-3 cells probably through regulating the expression of miRNAs. Interruption of miRNA profiling may provide new therapeutic methods for the clinical treatment of pancreatic cancer.